Variation of heat flux and its effect on the reproduction of four major Chinese carp - Wenxian Guo; Wenxiong Chen; Ning He; Hongxiang Wang (Water Supply, 2023)
River heat flux (HF) regime has been significantly affected by anthropogenic activities and climate variation, and it is of great significance to deeply explore intrinsic driving mechanisms and ecological effects. This study uses the middle reaches of the Yangtze River as its research area and, by constructing the wavelet model and the IHA-RVA model, quantifies the evolution mechanism and internal law of ‘flow- water temperature (WT) – HF’ over the past four decades and investigates the effects of Three Gorges Dam on the ecological reproduction of ‘four major Chinese carp’. The results show that, (1) flow and WT have three change cycle scales; the overall hydrologic variations of flow and WT were 64% and 62%, respectively, close to high variation. (2) The overall HF shows a decreasing trend from 1983 to 2019, with significant changes in HF in spring and winter regulated by the Three Gorges Reservoir; the basin flow-WT-HF relationships exhibit a hysteretic pattern, with the maximum WT occurring one month after the peak HF and flow. (3) The ‘four major Chinese carp’ natural breeding season is closely related to the time when the WT reaches 18 °C; HF is a vital habitat factor that influences fish spawning and reproduction. HIGHLIGHTS Analysis of flow and water temperature changes in the upper reaches of Yangtze River based on wavelet analysis and IHA-RVA model.; Variation of heat fluxes in the upper reaches of the Yangtze River around 2003.; Heat flux is one of the important influencing factors on the spawning output of four major Chinese carp, and the suitable heat flux range for spawning of four major Chinese carp is identified.;